2003
DOI: 10.1055/s-2003-39498
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Injuries in Long-Distance Triathletes

Abstract: Triathlon is an individual sport consisting of three disciplines - swimming, cycling and running. Triathlon has changed from a novel appearance to a very popular Olympic sport within the last fifteen years. Nevertheless, there is not sufficient data about injuries in triathlon. The aim of this retrospective survey was to investigate the incidence of injuries according to class of injuries, anatomical sites and disciplines. Relations to age, sex, performance level, training habits and medical care were analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
2
19

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(97 citation statements)
references
References 12 publications
3
73
2
19
Order By: Relevance
“…The prevalence of trauma injuries in triathletes in this study (52.4%) is higher than that found by Collins et al 4 and Korkia et al 9 but lower than that found by Egermann et al, 1 Wilk et al, 6 and O'Toole et al 5 The prevalence is also lower than suggested by our preliminary study (62.8%) who had examined 43 triathletes. 2 The distribution of injury suggested by our preliminary study 2 is remarkably confirmed by the results of this study: 44.5% of triathletes reported having made a tendinopathy during the previous season (vs. 41.9% in the preliminary study) and 35% muscle injury (vs. 37%).…”
Section: Discussioncontrasting
confidence: 66%
See 4 more Smart Citations
“…The prevalence of trauma injuries in triathletes in this study (52.4%) is higher than that found by Collins et al 4 and Korkia et al 9 but lower than that found by Egermann et al, 1 Wilk et al, 6 and O'Toole et al 5 The prevalence is also lower than suggested by our preliminary study (62.8%) who had examined 43 triathletes. 2 The distribution of injury suggested by our preliminary study 2 is remarkably confirmed by the results of this study: 44.5% of triathletes reported having made a tendinopathy during the previous season (vs. 41.9% in the preliminary study) and 35% muscle injury (vs. 37%).…”
Section: Discussioncontrasting
confidence: 66%
“…5,21---25 On the over side, the competitive practice was similar to that described by other authors. 1 As suggested by Korkia et al, 9 the training loads reported by the amateur triathletes seem very important, especially among men (9.2 hours per week on average). These results and the nature of injury suggest probable errors in the planning of training.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations